1986
DOI: 10.4319/lo.1986.31.1.0149
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nitrogen uptake by epilithic periphyton in a N‐deficient lake1

Abstract: Seasonal patterns of dissolved inorganic nitrogen and inorganic carbon uptake by the sublittoral epilithic periphyton community in N-deficient, oligotrophic Lake Tahoe were examined. The biomass dominants of this community, N,-fixing blue-green algae (e.g. Calothrix, Tolypothrix, and Nostoc) were persistent and retained their nitrogenase activity throughout the year. Seasonal rates of N, fixation exhibited considerable variation, with a distinct summer maximum and winter minimum. Uptake of both N03-and NH4+ fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…C : N : P ratios were reported from studies dealing with microphytobenthos before, but they were reported without relating them to growth rates. The ratios were in the range reported here (Reuter et al 1986;Engle and Melack 1993;Rosemond 1993;Rosemond et al 1993;Turner et al 1994;Vymazal and Richardson 1995;Hillebrand and Sommer 1997). Therefore, the limits for nutrient ratios proposed by us can be applied for periphyton dominated by diatoms and cyanobacteria.…”
mentioning
confidence: 55%
“…C : N : P ratios were reported from studies dealing with microphytobenthos before, but they were reported without relating them to growth rates. The ratios were in the range reported here (Reuter et al 1986;Engle and Melack 1993;Rosemond 1993;Rosemond et al 1993;Turner et al 1994;Vymazal and Richardson 1995;Hillebrand and Sommer 1997). Therefore, the limits for nutrient ratios proposed by us can be applied for periphyton dominated by diatoms and cyanobacteria.…”
mentioning
confidence: 55%
“…Planktonic microbes exhibited higher P uptake rates than benthic microbes, which was in accordance with our hypothesis. Since these 2 distinct communities occupy different niches in aquatic systems (benthic vs. pelagic), there is no reason to believe that their physiological ecology should be similar (Reuter et al 1986). Additionally, the P concentration required to saturate growth for benthic microbes is much greater compared to planktonic (Reynolds 2006), likely due to the growth form of benthic assemblages (Hill et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Calibration with ethylene standards was conducted both prior to and after sample analysis each day, and an interlab calibration with known ethylene concentrations and 25 random samples (Freshwater Institute, Winnipeg, Canada). A time-series experiment was conducted, and rates of ethylene production were found to be linear between 0.5 and 2.5 h. Rates of N 2 fixation were calculated by use of a theoretical 4 : 1 (C 2 H 2 : N 2 ) conversion ratio, which is of similar magnitude to experimentally determined conversion ratios for epilithic algal communities (Reuter et al 1986;Larkum et al 1988).…”
Section: Epilithic Nitrogen Fixation In the Rocky Littoral Zones Of Lmentioning
confidence: 99%